Exploring Business Perceptions of the Compliance Costs of Regulation - Lewis , Phil; Richardson , Alice; Corliss , Michael (Journal of Law and Governance, 2015)
The compliance costs of regulation borne by businesses operating in Australia are of growing concern, particularly the disproportionate impact upon small business. This paper uses correspondence analysis on a survey of businesses in NSW and Victoria to further investigate the links between the characteristics of businesses such as firm size, difficulty with various types of regulation and external advice. The main findings of this paper are that although there is a positive relationship between firm size and difficulty complying with government regulation, the level of difficulty seems to have a minimum level even for the very small firms. Furthermore it appears that certain types of external advice, particularly advice from accountants, may operate to significantly reduce the difficulty firms have maintaining compliance.